Women's advancement to senior management positions in the Department of Rural Development and Land Reform - Ngomane, Sipho (My University, 2018)
The advent of a democratic South Africa in 1994 saw the implementation of legislative and strategic frameworks aimed at balancing opportunities for both men and women at the workplace. The primary focus of these frameworks was implementation of measures to advance women to enable them access to opportunities previously barred to them. Female representation in senior management positions remains skewed despite frameworks put in place to correct such imbalances. In such instances where women were promoted to senior management positions, literature shows they are often met with challenges which hinder their advancement. This study sought to explore perceptions of barriers women senior managers encounter in senior management positions at the Department of Rural Development and Land Reform (DRDLR). A qualitative approach was the preferred method of research, using a single case study. The researcher triangulated data using questionnaires, semi-structured interviews, and documentary evidence. Thematic analysis was used to analyse data. Findings revealed that although the department has partially met the numerical target of women in senior management positions, there are organisational or systemic barriers, professional career pipeline barriers and institutional climatic barriers. The study concludes that direct and indirect barriers exists which hinder women‟s advancement in the DRDLR. Organisational development interventions are recommended to address the identified barriers at personal and organisational level.
A research report submitted to the Faculty of Management, University of the Witwatersrand, in 25% fulfilment of the requirements for the degree of Master of Management (in the field of Public and Development Management). February, 2018
Keywords: Women in education; Women in public life--South Africa